Microplastic-associated biofilms as reservoirs for Vibrio spp. And tetB in urban rivers of Eastern Cape, South Africa - Nnadozie, Havilah Onyinyechi (Rhodes University, 2026)
Microplastic (MP) pollution has become a significant concern, as these small particles can persist, accumulate and contribute to the persistence and spread of waterborne pathogens such as Vibrio spp. and antibiotic resistance genes (ARGs) such as tetB in freshwater systems. MPs can originate from intentional production (primary MPs) or the weathering of larger plastics (secondary MPs). In South Africa, the interconnected issues of plastic pollution, water quality management and microbial contamination of water sources remain insufficiently addressed, especially regarding microplastics which can carry pathogens and antibiotic resistance genes (ARGs) and may pose significant risks to environmental and public health. Amidst the rising cholera and vibriosis incidences in South Africa, this study assessed the role of MP biofilms in the enrichment of Vibrio spp. and tetB in the Kat and Swartkops rivers, Eastern Cape, South Africa, and thus their potential role in persistence of antibiotic resistance and waterborne infections. A literature review was conducted to examine MP pollution in aquatic environments, MP role in harbouring antibiotic-resistant bacteria (ARB) and ARGs, including Vibrio spp. and tetB, as well as to elucidate methodological approaches for analysing MP biofilm communities and ARGs in rivers. Thereafter, water and MPs were sampled from ten sites along the Kat and Swartkops rivers impacted by various land uses in March and July 2023. Concurrently, physicochemical parameters of the river water including temperature, salinity, dissolved oxygen, turbidity, nitrates, nitrites, phosphates and ammonia were measured to assess their potential as drivers of Vibrio and tetB in these environments. Microplastic particles were visualised using stereo microscopy, counted and classified into four groups based on their shape. Novel primers targeting the recA gene were designed and evaluated in-silico and experimentally for enhanced detection of Vibrio directly from river water samples. A comparative analysis of this primer with the previously published and widely used Vibrio spp. 16S rRNA primer (V.16S-700F/1325R) was conducted to assess their relative specificity, sensitivity and amplification efficiency. The primer with superior performance was thereafter used for Quantitative Polymerase Chain Reaction (qPCR) to measure the relative abundance of Vibrio spp. 16S rRNA and tetB genes. A comparative CT method (2−ΔCT) was used to calculate the relative abundance of Vibrio spp. 16S rRNA and tetB per total bacteria (via 16S rRNA gene) in water and MP biofilms. Lastly, findings from the quantitative assessments of Vibrio spp. and tetB gene prevalence were analysed in relation to water physicochemical parameters. The MP abundance ranged from 0.69 to 4.03 particles/L with a mean of 1.52 particles/L in the Swartkops River, and 0.74 to 2.20 particles/L with a mean of 1.55 particles/L in the Kat River. MP fragments were the most abundant type of microplastic, followed by fibres, films and pellets. In both rivers, the sites downstream of wastewater treatment effluent discharge points showed the highest MP abundance. Compared to the primer designed in this study, the 16S rRNA primer demonstrated superior performance, achieving a higher sensitivity (LOD = 103 gene copies/μL). For amplification efficiency, positive signals were observed between 107 to 103 gene copies/μL, yielding a regression coefficient (R²) of 0.999, a slope of -3.75, and an efficiency of 85%. Melt curve analysis revealed a single peak at 88.16 ± 0.15°C, confirming amplification specificity. In contrast, the recA primer exhibited a lower sensitivity (10⁴ gene copies/μL) and slightly lower detection rates of Vibrio spp., at 95% of river water samples and 42% of biofilm samples, compared to 100% detection in water and MP biofilms by the 16S rRNA primer. The relative abundance of Vibrio 16S rRNA ranged from 9.46 x 10-3 to 1.86 copies/16S rRNA in water and 4.66 x 10-3 to 0.82 copies/16S rRNA in MP biofilms. In contrast, tetB relative abundance ranged from 1.60 x 10-8 to 1.55 x 10-4 copies/16S rRNA in water and 9.51 x 10-8 to 8.46 x 10-4 copies/16S rRNA in MP biofilms. However, there was no significant difference in the gene abundances between water and the MP biofilm (Student t-test, p > 0.05). Spearman’s rank correlation analysis revealed moderate correlations between river physicochemical conditions and Vibrio 16S rRNA and tetB in both rivers. Additionally, land use factors such as wastewater treatment discharge, agricultural runoff and industrial effluents were found to influence Vibrio spp. and tetB abundances. These findings do not support the assumption that MPs enrich bacterial pathogens and their ARGs, including Vibrio and tetB. Instead, the study identifies anthropogenic sources, particularly wastewater treatment works (WWTW), as a primary driver of bacterial and ARG abundance in urban rivers. These findings call for improved WWTW infrastructure to mitigate microplastic contamination and the proliferation of ARB and ARGs in urban rivers. Significantly, there is a need for interventions that consider multiple river pollution sources, instead of focusing solely on MPs to mitigate ARB and ARG dissemination.
the role of microplastics in the enrichment and persistence of pathogens and antibiotic resistance genes
Keywords: Uncatalogued